NANOSIZE SCALE ADDITIVES MIX INFLUENCE ON THE PROPERTIES OF THE HIGH PERFORMANCE CONCRETES - Ponomarev, Andrey; Knežević, Miloš; Vatin, Nikolay; Kiski, Svetlana; Ageev, Ilya (Journal of Applied Engineering Science, 2014)
It was experimentally founded, that the size and the topology of the particles the active additives in the composition of new kinds of high performance concretes is a very important parameter (as its chemical activity), especially if the combination of this additives possible to realize the nonlinear phenomena. The sample of  the combination of high disperse silica fume and nanocarbon particles fulleroid type - Astralenes®.was researched. It was founded also the possibility of high level of increasing the life-time of polymer components in composite concretes due the presence the fulleroid type nanoparticles.
Keywords: Life-time of polymer components; Improved pressure strength; Improved mobility of concrete solution; Optimal structure of the cement stone; Astralenes®; Silica fume; Micro amount of additives; Nanosize scale additives mix